Enhancing Canada's sustainable development goals: Leveraging neutrosophic programming for agenda 2030 - Anas Melethil; Nabil Ahmed Khan; Golam Kabir; Ahmad Yusuf Adhami; Irfan Ali (Environmental and Sustainability Indicators)
The study employed neutrosophic programming to optimize Canada's efforts toward achieving the Sustainable Development Goals (SDGs) by 2030. It focused on maximizing GDP and employment while minimizing carbon emissions and electricity consumption. The findings indicated substantial progress in GDP and employment, with GDP projections aligning closely with ARIMA forecast values. However, the optimization results for reducing carbon emissions and electricity consumption were less favorable, as both exceeded the 2030 targets, though slightly below ARIMA forecasts. These outcomes underscore the ongoing challenge of balancing economic growth with environmental sustainability. Neutrosophic programming proved effective in managing uncertainties and imprecise data, particularly in addressing complex, sometimes conflicting objectives like those within the SDGs. Future strategies include advancing greener technologies in high-emission sectors, introducing policy measures such as incentives for renewable energy, stricter emissions regulations, subsidies for green technologies, and increasing investment in sustainable technology research and development.